Pendidikan Hukum Dan Advokasi Untuk Masyarakat Marginal: Meningkatkan Kesadaran Dan Akses Keadilan - Hermansyah; Kurniawan; Al-Munip; Ahmad Ihya' Ulumuddin (Vonis, 2025)
This study aims to analyze the effectiveness of community-based legal education and advocacy in enhancing legal awareness and expanding access to justice for marginalized communities. These groups often face structural and cultural barriers in exercising their legal rights due to limited knowledge, restricted access to information, and insufficient legal resources. Employing a qualitative descriptive approach, the research was conducted in three urban areas with low-income populations. Data were collected through participatory observation, in-depth interviews, and documentation from legal aid institutions (LBH), and analyzed using the interactive model of Miles and Huberman. The findings indicate that community-based legal education has improved public legal understanding by up to 68%, encompassing awareness of legal rights and obligations, reporting mechanisms, and the principle of equality before the law. The participatory and contextual approach proved effective by providing learning experiences relevant to the participants’ social realities. Local paralegals played a crucial role as intermediaries between communities and formal legal institutions, strengthening both advocacy independence and program sustainability. The study highlights the importance of multi-stakeholder collaboration among legal aid organizations, academia, and local governments in developing an inclusive and sustainable model of community legal empowerment. Thus, legal education functions not only as a medium for enhancing legal literacy but also as an instrument of social transformation toward a legally conscious, empowered, and just society.